2007
DOI: 10.1094/fg-2007-1108-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Harvest Management on Rhizoma Perennial Peanut Production, Nutritive Value, and Persistence on Flatwood Soils

Abstract: Rhizoma perennial peanut (RPP), Arachis glabrata Benth., has high nutritive value, is long lived, and drought tolerant; however, its growth and persistence on flatwood soils (spodosols) common in south Florida is thought to be poor. The objective of this study was to determine the influence of harvest management (stubble height, 1 vs 4 inches) and RPP entries [Arbrook Select (local ecotype), ‘ Arbrook’(released cultivar), PI 262839, PI 262826, ‘ Florigraze’(released cultivar), Ecoturf (PI 262840), and PI 26283… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…At Ona, UF Tito generally was not different in DM yield from most other entries in the test. Yields at this location were relatively consistent over the experiment, with only a slight decrease in DM yields over the period of the experiment, whereas other selections decreased in persistence and yield (Mislevy et al, 2007). At Citra, UF Tito generally had greater DM yield than Florigraze and Ecoturf but was not different from Arbrook and UF Peace.…”
Section: Characteristicsmentioning
confidence: 79%
See 1 more Smart Citation
“…At Ona, UF Tito generally was not different in DM yield from most other entries in the test. Yields at this location were relatively consistent over the experiment, with only a slight decrease in DM yields over the period of the experiment, whereas other selections decreased in persistence and yield (Mislevy et al, 2007). At Citra, UF Tito generally had greater DM yield than Florigraze and Ecoturf but was not different from Arbrook and UF Peace.…”
Section: Characteristicsmentioning
confidence: 79%
“…Most of the research with RP over the past two decades has focused on methods for improved establishment (Canudas et al, 1989; Kelly and Quesenberry, 1993; Williams et al, 1997), utilization under grazing (Ortega‐S. et al, 1992), and evaluation of new germplasm accessions (Freire et al, 2000; Mislevy et al, 2007; Ruttinger‐Lamperti, 1989; Williams et al, 2008). The early research (Prine et al, 1981) showed that most accessions of RP produce very small amounts of seed.…”
mentioning
confidence: 99%
“…Similarly, as grazing intensity increased, Florigraze root-rhizome mass and TNC concentration decreased markedly during 2 yr (Rice et al, 1995). After 4 yr of clipping to SH of 2.5 and 10 cm, Ecoturf root-rhizome mass was twice as great for the 10-as the 2.5-cm SH, but percentage Ecoturf cover remained high at 76% for the short SH (Mislevy et al, 2007). A previous report showed that Ecoturf had greater root-rhizome mass than Florigraze under a range of grazing treatments (4450 and 3490 kg ha −1 , respectively; Mullenix et al, 2016b).…”
Section: Root-rhizome Mass and Total Nonstructural Carbohydrate Poolmentioning
confidence: 92%
“…1). Previous reports include 8.3 to 12 Mg ha −1 yr −1 during a 4-yr clipping trial in north-central Florida , 10.8 Mg ha −1 yr −1 across 4 yr under clipping in south Florida (Mislevy et al, 2007), up to 13 Mg ha −1 yr −1 in northwest Florida (Dubeux et al, 2017), and 6.0 to 9.2 Mg ha −1 yr −1 during 2 yr of grazing in north-central Florida (Mullenix et al, 2016a). Herbage accumulation responses in the current study are generally within or slightly greater than the range reported in the literature.…”
Section: Herbage Accumulationmentioning
confidence: 99%
See 1 more Smart Citation